(untitled) - Emel Bahadir-Yilmaz (University of Ostrava, 2021)
Aim: The study aimed to investigate the relationship between nursing students' exposure to colleague violence and stress levels in nursing education. Design: A correlational research design was chosen for the study. Methods: The study was implemented with 206 nursing students at a state university in northeast Turkey. Data were collected using the Scale of Exposure to Colleague Violence and the Nursing Education Stress Scale and analyzed using descriptive statistics and the Spearman correlation test. Results: The nursing students' mean age was 21.59 (± 1.88) (min. = 20; max. = 40); 75.2% were female; 77.7% were from a nuclear family; and 77.2% stated that their income was equal to their expenses. The colleague violence score of the students was 63.29 (± 17.29) and the nursing education stress score was 53.67 (± 19.42). A positive and moderate relationship was found between the total colleague violence score and total nursing education stress score (p < 0.01). A positive and moderate relationship was also determined between exposure to verbal / psychological violence and nursing education stress (p < 0.01). Moreover, a positive and moderate relationship was observed between the effect of violence on physical and mental health and nursing education stress (p < 0.01). Conclusion: Results indicated that nursing students who were exposed to colleague violence during clinical practice experienced practical and academic stress. Nurses should be aware that colleague violence is an ethical problem concerning respect for human dignity.